2019
DOI: 10.1155/2019/4642701
|View full text |Cite
|
Sign up to set email alerts
|

Numbness and Weakness Recovered at a Less Extent in Patients with Lumbar Disc Herniation after Percutaneous Endoscopic Lumbar Discectomy

Abstract: Background. Patients with lumbar disc herniation (LDH) may present with motor disorders and various sensory disorders, among which pain and numbness are the most common ones. Percutaneous endoscopic lumbar discectomy (PELD) is reported to be both safe and effective. However, most of the previous studies focused on the recovery of pain, and the relief extent of numbness and weakness has rarely been reported. The Sciatica Bothersomeness Index (SBI) is a self-assessment tool for LDH patients. It has demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
11
2
1
Order By: Relevance
“…Sciatica, numbness, and weakness of lower extremes were common manifestations of LDH, therefore this study assessed the relationship between these symptoms and the severity of SIJ degeneration further (40). We found that LDH with sciatica, numbness, and/ or weakness suffered from more severe degradation of SIJ.…”
Section: E363mentioning
confidence: 88%
“…Sciatica, numbness, and weakness of lower extremes were common manifestations of LDH, therefore this study assessed the relationship between these symptoms and the severity of SIJ degeneration further (40). We found that LDH with sciatica, numbness, and/ or weakness suffered from more severe degradation of SIJ.…”
Section: E363mentioning
confidence: 88%
“…24 Moreover, sensitive impairment shows a weaker correlation with ODI score when compared with pain score and motor deficit, thus suggesting a lesser influence on social dysfunction. 25 Another possible limitation may be the fact that MRI images have been classified by only 1 reader; thus, the study considered neither intra-rater nor interrater variability. The comparison between the classification results of several raters may be useful to assess the generalization capability of the MSU classification for the indicated purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous discectomy: Percutaneous discectomy is effective and can be used as a treatment for LDH with radiculopathy[ 34 - 36 ] (recommended level B, level of evidence 2b), but the application is strictly limited to the indications[ 37 ].…”
Section: Treatmentmentioning
confidence: 99%